Effects of selection of inlet perturbations, multiphase and turbulence equations on slug flow characteristics using altairÂ® acusolveâ¢ - Basith, M.S.A. (MDPI, 2021)
Selection of inlet perturbations, multiphase equations, and the turbulence equation may affect the development of slug flow using computational fluid dynamic simulation tools. The inlet perturbation, such as sinusoidal and random perturbations, play an essential role in inducing slug formation. Multiphase equations such as volume of fluid and level set methods are used to track and capture the gas-liquid immiscible interface. Similarly, turbulence equations such as Spalart Allmaras (SA), Detached Eddy Simulations (DES), k-omega, and k-epsilon can be used to predict the evolution of turbulence within the flow. At present, no direct comparison is available in the literature on the selection of (i) types of inlet perturbations, (ii) the choice of multiphase equations, and (iii) the turbulence equation on the development of slug flow using the Altair computational package. This article aims to compare the effects of the selection of inlet perturbations, multiphase models and turbulence equations on slug flow characteristics using AltairÂ® AcuSolveâ¢. The findings by AltairÂ® simulation were compared to published experimental data and simulation works using ANSYS and STAR-CCM+. The slug flow characteristics of interest include slug morphology, a body length-to-diameter ratio, velocity, frequency, and pressure gradient. It was found that the slug flow could be developed for all combinations of settings. Although level set approach in AltairÂ® can track fluid motion successfully, it has a limitation in modelling the convective transport of the multiphase mixture well, unlike ANSYS and STAR-CCM+. Compared to the standard level set method, the coupling of back-and-forth error compensation and correction with the level set function helps to capture the internal boundary more accurately by reducing errors caused by numerical diffusion in the transport of the level set. It was revealed that the Spalart Allmaras turbulence equation could mimic published experimental result better than DES as it produced the closest slug translational velocity. Since the frequency of the slugs for the developed models showed a good agreement with the published data, the models could be sufficient for the investigation of fluid-structure interaction. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.